PENGARUH VITAMIN C TERHADAP KADAR SERUM FERITIN PADA PASIEN GAGAL GINJAL KRONIK DENGAN HEMODILISIS REGULER - Wiryani, Cilik; Suwitra, Ketut (journal of internal medicine, 2010)
Hyperferitinemia in chronic kidney disease patients with regular hemodyalisis may caused by repeated transfusion,excessive iron supplementations, and also inß ammation. Increasing of serum feritin level doesn!t depend on iron reservecapacity. Hemodialysis patients with no supplementations may lead to several antioxidant components deÞ ciency. Qualitative andquantitative of vitamin C deÞ ciency may also occur, thus administration 1